Public debt in Nepal: an assessment - Bhattarai, Kumar (Economic Journal of Development Issues, 2015)
Public debt is the instrument of financing budget deficit. One important macroeconomic problem of Nepalese economy is prevailing resource gap. Due to such situation, with the increase in size of government budget, the size of public debt is also increasing. With the increase in public debt, it is worthwhile to study how macroeconomic indicators are changing over the time. This study is based on the descriptive analysis. For this purpose, the period of 1975/76-2010/11 is considered. In this period, public debt has increased, on average, by 18.86%. The share of external loan, on average, seems to be relatively higher, i.e. 58.85% whereas such share of internal loan is 41.15%. However, in the latter period, the share of internal loan has significantly higher than the share of external loan. For example, during the period of 2005/06-2010/11, the average share of internal loan is 68.01% whereas such share of external loan is 31.99%. In spite of increased budget and increased public debt, the growth rate of economy is relatively low. On average, it is 4.28%. But, the rate of inflation is, on average, 8.31%. Thus, Nepalese economy is facing the problem of low rate of economic growth and high rate of inflation.DOI: http://dx.doi.org/10.3126/ejdi.v15i1-2.11864Economic Journal of Development Issues Vol. 15 & 16 No. 1-2, pp. 50-59